Protected areas for environmental sustainability in Nigeria - OI Imasuen; JN Oshodi; TUS Onyeobi (Journal of Applied Sciences and Environmental Management)
This paper is focused on protected areas for environmental sustainability in Nigeria. It has examined what protected areas are the meaning,  especially as defined by the International Union for the Conservation of Nature (IUCN). A thorough investigation was done to identify the areas that were and are still protected in Nigeria. In this regard we have identified some parks and other areas of special interests within our environment that may have been preserved for aesthetics and environmental sustainability. The historical background of protected areas in Nigeria was examined particularly in relation to the development drive and industrial growth. Attempt was then made to determine if the country has lost its bearings with regards to the role of cultural heritage and the natural environment. In this respect, comparisons were made between the modern cities/towns and the old ones in Nigeria. The role of the traditional knowledge in environmental sustainability was also examined. We then considered the status of protected areas and environmental sustainability. Finally we are suggesting guidelines for the next level which is the necessary steps urgently needed; that is “strategies for protected areas